2006
DOI: 10.1109/tsp.2006.879313
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Fractional Fourier Transform Based on New Nearly Tridiagonal Commuting Matrices

Abstract: Based on discrete Hermite-Gaussian-like functions, a discrete fractional Fourier transform (DFRFT), which provides sample approximations of the continuous fractional Fourier transform, was defined and investigated recently. In this paper, we propose a new nearly tridiagonal matrix, which commutes with the discrete Fourier transform (DFT) matrix. The eigenvectors of the new nearly tridiagonal matrix are shown to be DFT eigenvectors, which are more similar to the continuous Hermite-Gaussian functions than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 21 publications
2
38
0
3
Order By: Relevance
“…However, authors in [67] believe that the discrete time counterparts of the continuous time Hermite-Gaussians maintained the same properties, since these discrete time counterparts exhibited better approximations than the other proposed approaches [68]. In order to resolve this issue about the approximation of Hermite-Gaussian functions, a nearly tri-diagonal commuting matrix of the DFT and a corresponding version of the DFRFT was proposed in [69]. Most of the eigenvectors of this proposed nearly tridiagonal matrix result in a good approximation of the continuous Hermite-Gaussian functions by providing a smaller approximation error in comparison to previous approaches.…”
Section: Dfrft Based On Eigenvectorsmentioning
confidence: 99%
“…However, authors in [67] believe that the discrete time counterparts of the continuous time Hermite-Gaussians maintained the same properties, since these discrete time counterparts exhibited better approximations than the other proposed approaches [68]. In order to resolve this issue about the approximation of Hermite-Gaussian functions, a nearly tri-diagonal commuting matrix of the DFT and a corresponding version of the DFRFT was proposed in [69]. Most of the eigenvectors of this proposed nearly tridiagonal matrix result in a good approximation of the continuous Hermite-Gaussian functions by providing a smaller approximation error in comparison to previous approaches.…”
Section: Dfrft Based On Eigenvectorsmentioning
confidence: 99%
“…For the DFRFT of type 2, the parameter " " is used to control the variation of the chirp in frequency domain [13]. The DFRFT of type 2 also needed "2 + ( /2)log 2 " multiplication operations.…”
Section: 12mentioning
confidence: 99%
“…The authors had derived another type of discrete fractional Fourier transform as reported in [13,[18][19][20][21][22][23][24][25] by searching the eigenvectors and eigenvalues of the DFT matrix followed by computing the fractional power of the DFT matrix based on Hermite function. This type of DFRFT worked very similarly to the continuous FRFT, and it fulfills the properties of orthogonality, additivity, and reversibility.…”
Section: Eigenvector Decomposition Type Dfrftmentioning
confidence: 99%
See 2 more Smart Citations